2022
DOI: 10.1002/ece3.8713
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the mitochondrial DNA d‐loop region reveals the maternal origin and historical dynamics among the indigenous goat populations in east and west of the Democratic Republic of Congo

Abstract: This study aimed at assessing haplotype diversity and population dynamics of three Congolese indigenous goat populations that included Kasai goat (KG), small goat (SG), and dwarf goat (DG) of the Democratic Republic of Congo (DRC). The 1169 bp d‐loop region of mitochondrial DNA (mtDNA) was sequenced for 339 Congolese indigenous goats. The total length of sequences was used to generate the haplotypes and evaluate their diversities, whereas the hypervariable region (HVI, 453 bp) was analyzed to define the matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…In contrast to the results of 13 coding and 2 ribosomal genes, sequences of the mitochondrial control region were suitable for differentiation the main maternal haplogroups from each other (Figure 2; Appendices Figure S16; Appendices Table S2). Our findings are well corroborated by previous research that used the control region in which the six highly divergent haplogroups in domestic goats were identified (Vacca et al, 2010;Ghernouti et al, 2017;Nguluma et al, 2021;Baenyi Simon et al, 2022).…”
Section: Phylogenetic Relationships Based On the 13 Protein Coding Ge...supporting
confidence: 91%
“…In contrast to the results of 13 coding and 2 ribosomal genes, sequences of the mitochondrial control region were suitable for differentiation the main maternal haplogroups from each other (Figure 2; Appendices Figure S16; Appendices Table S2). Our findings are well corroborated by previous research that used the control region in which the six highly divergent haplogroups in domestic goats were identified (Vacca et al, 2010;Ghernouti et al, 2017;Nguluma et al, 2021;Baenyi Simon et al, 2022).…”
Section: Phylogenetic Relationships Based On the 13 Protein Coding Ge...supporting
confidence: 91%
“…The high genetic variation observed within populations could be attributed to a lack of selective breeding, random mating within the population, mutations that can generate completely new alleles in a population, or even reshuffling of alleles within an organism's offspring during homologous recombination [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the median joining network revealed that the populations from Ghana have little divergence and share the most common haplotypes between the three agro-ecological zones. Less-divergent haplotypes within animals and geographical locations suggest that gene flow has occurred on a regional scale during the recent past and the animals have not been subdivided by long-term biogeographic barriers (Simon et al, 2022). The AGC populations from Tanzania on the other hand were more structured with some haplotypes unique to a single population (Udzungwa South) while other haplotypes were shared between populations (Udzungwa North, Uluguru urban and Uluguru rural), indicating low genetic exchange among the Udzungwa South, Udzungwa North, and Uluguru urban and rural populations.…”
Section: Discussionmentioning
confidence: 99%